Novel strains of a pandemic plant virus, tomato spotted wilt orthotospovirus, increase vector fitness and modulate virus transmission in a resistant host - Chinnaiah, Senthilraja; Gautam, Saurabh; Herron, Benjamin; Workneh, Fekede; Rush, Charles M.; Gadhave, Kiran R. (Frontiers in Microbiology, 2023)
Tomato spotted wilt orthotospovirus (TSWV) is one of the most successful pandemic agricultural pathogens transmitted by several species of thrips in a persistent propagative manner. Current management strategies for TSWV heavily rely on growing single gene resistant cultivars of tomato ('Sw-5b' gene) and pepper ('Tsw' gene) deployed worldwide. However, the emergence of resistance breaking strains (RB) in recent years has compounded the threat of TSWV to agricultural production worldwide. Despite this, an extensive study on thrips transmission biology of RB strains is currently lacking. It is also unclear whether mutualistic TSWV-thrips interactions vary across different novel strains with disparate geographical origins. To address both critical questions, we studied whether and how four novel RB strains of TSWV (two sympatric two allopatric) along with a non-RB strain, impacts western flower thrips (WFT) fitness and whether this leads to differences in TSWV incidence, symptoms severity (virulence) and virus accumulation in two differentially resistant tomato cultivars. Our findings show that all RB strains increased WFT fitness by prolonging the adult period and increasing fecundity compared to non-RB and non-viruliferous controls regardless of the geographical origin of strains or the TSWV titers in individual thrips, which were substantially low in allopatric strains. TSWV accumulation in thrips varied at different developmental stages and was unrelated to infected tissues from which thrips acquired the virus. However, it was significantly positively correlated to that in WFT-inoculated susceptible plants, but not the resistant ones. The TSW incidences were high in tomato plants infected with all RB strains, ranging from 80-90% and 100% in resistant and susceptible plants, respectively. However, TSW incidence in the non-RB infected susceptible tomato plants was 80%. Our findings provide new insights into how novel strains of TSWV, by selectively offering substantial fitness benefits to vector, modulate transmission and gain a potential epidemiological advantage over non-RB strains. This study presents the first This is a provisional file, not the final typeset article direct evidence of how vector-imposed selection pressure, besides the one imposed by resistant cultivars one may contribute to the worldwide emergence of RB strains.